A 12,000-year-old clay figurine of a woman and a goose marks symbolic innovations in Southwest Asia - Laurent Davin; Natalie D. Munro; Leore Grosman (Proceedings of the National Academy of Sciences, 2025)
Paleolithic representations of human–animal interaction are rare, with only a few painted or engraved examples recorded in Upper Paleolithic contexts, mostly from Europe. Such scenes, depicting real or imagined interactions, are of major importance for understanding a wide range of past human perspectives, starting with how people conceived of their ontological relationship with the environment and nonhuman beings. In the Early Neolithic in Southwest Asia, shifts in perspective led human communities to manipulate and transform their environment while simultaneously depicting new forms of art featuring human–animal interactions. Here, we describe the recent discovery of the earliest figurine depicting a human–animal interaction—a woman and a goose—from the Late Epipaleolithic (c. 12,000 years cal. BP) village of Nahal Ein Gev II in northern Israel. The artistic techniques and raw materials that were used and the mythological scene that was depicted appear earlier than previous examples, foreshadowing the more monumental changes in symbolic expression that occur in the following Neolithic periods. Through technological, archaeometric, and dermatoglyphic analyses, we demonstrate that this unique figurine was meticulously modeled from clay using innovative techniques that created perspective using form and light. Importantly, the figurine captures a mythological scene between the woman and the goose that is consistent with an animistic belief system. Through our combined multidisciplinary approach, this study provides important original data regarding the antiquity and development of symbolic expression using clay at the end of the Epipaleolithic at a crossroads between early sedentary and fully Neolithic societies in Southwest Asia.